Eva Gore-Booth : an image of such politics - Tiernan, Sonja (Manchester University Press, 2012)
"This is the first dedicated biography of the extraordinary Irish woman, Eva Gore-Booth. Gore-Booth rejected her aristocratic heritage, choosing to live and work among the poorest classes in industrial Manchester. Her work on behalf of barmaids, circus acrobats, flower sellers, and pit-brow lasses is traced in this book. During one impressive campaign, Gore-Booth orchestrated the defeat of Winston Churchill. Gore-Booth published volumes of poetry, philosophical prose, and plays, becoming a respected and prolific author of her time and part of W.B. Yeats' literary circle. The story of Gore-Booth's life is captivating. Her close bond with her sister, an iconic Irish nationalist, provides a new insight into Countess Markievicz's personal life. Gore-Booth's life story vividly traces her experiences of issues such as militant pacifism during the Great War, the case for the reprieve of Roger Casement's death sentence, sexual equality in the workplace, and the struggle for Irish independence."--Publisher's website